Physiological potential of the chlorophyte Caulerpa prolifera for proliferation across the Mediterranean-Atlantic basins in a warmer ocean - Olivé, Irene (2021)
Ocean warming is altering the metabolic balances of organisms, favouring the expansion of thermo-tolerant individuals. The fast-growing macroalga Caulerpa prolifera is rapidly expanding in the Ria Formosa lagoon (Portugal), a connection area between Mediterranean and Atlantic basins. We investigated the metabolic capacity of C. prolifera to cope with ocean warming, to elucidate its expansion potential. The photosynthetic and respiratory plasticity of 4 populations of C. prolifera spread along the Mediterranean−Atlantic basins was assessed under a temperature range of 20 to 30°C. In addition, molecular markers were used to investigate the genetic identity of the strain found in Ria Formosa, which confirmed its Mediterranean origin. All examined populations showed large physiological thermo tolerance and metabolic plasticity to warming. The photosynthetic efficiency of C. prolifera improved by 50% with temperature, and the maximum photosynthetic production doubled along the temperature range tested. Respiration did not vary with temperature, whereas the metabolic quotient increased by more than 70%when temperature increased from 20 to 25−30°C. Minor differences in the photosynthetic descriptors were detected among populations, reflecting light- and dark-adapted physiology of Mediterranean and Atlantic populations, respectively. Our results show that all tested populations of C. prolifera have the physiological potential to cope with temperature increases up to 30°C, which indicates that ocean warming may contribute to the expansion of C. prolifera in the Mediterranean− Atlantic basins.